Modifiable vascular risk factors in patients with cerebral and spinal cavernous malformations: a complete 10‐year follow‐up study. (23rd February 2023) - Rauscher, Steffen; Santos, Alejandro N.; Gull, Hanah Hadice; Rauschenbach, Laurèl; Chen, Bixia; Schmidt, Börge; Deuschl, Cornelius; Benet, Arnau; Jabbarli, Ramazan; Wrede, Karsten H.; Siegel, Adrian M.; Lawton, Michael; et al.
Abstract: Background and purpose: The aim was to investigate the effect of modifiable vascular risk factors on the risk of first and recurrent bleeding for patients with a cavernous malformation (CM) of the central nervous system (CNS) over a 10‐year period. Methods: A retrospective review of our CM institutional database was performed spanning from 2003 to 2021. The inclusion criteria were non‐missing serial magnetic resonance imaging studies and clinical baseline metrics such as vascular risk factors. The exclusion criteria were patients who underwent surgical CM removal and patients with less than a decade of follow‐up. Kaplan–Meier and Cox regression analyses were performed to determine the cumulative risk (10 years) of hemorrhage. Results: Eighty‐nine patients with a CM of the CNS were included. Our results showed a non‐significant increased risk of hemorrhage during 10 years of follow‐up in patients using nicotine (hazard ratio 2.11, 95% confidence interval 0.86–5.21) and in patients with diabetes (hazard ratio 3.25, 95% confidence interval 0.71–14.81). For the presence of modifiable vascular risk factors at study baseline different cumulative 10‐year risks of bleeding were observed: arterial hypertension 42.9% (18.8%–70.4%); diabetes 66.7% (12.5%–98.2%); hyperlipidemia 30% (8.1%–64.6%); active nicotine abuse 50% (24.1%–76%); and obesity 22.2% (4%–59.8%). Overall cumulative (10‐year) hemorrhage risk was 30.3% (21.3%–41.1%). Conclusions: The probability of hemorrhage in untreated CNS CM patients increases progressively within a decade of follow‐up. None of the modifiable vascular risk factors showed strong indication for an influence on hemorrhage risk, but our findings may suggest a more aggressive course in patients with active nicotine abuse or suffering from diabetes.